Emmanuel Levinas’s concept of interreligious dialogue: ethics of alterity in the age of religious plurality - Imran, Muzzamel Hussain (British Journal of religious education, 2025)
In our contemporary era, the increasing awareness of diverse religious traditions and the direct interaction with individuals from various faiths and cultures have reshaped the way we perceive religious plurality. This study aims to show a connection between Emmanuel Levinas’ ethics of alterity and interreligious dialogue, exploring whether Levinas’ philosophy can serve as a framework for openness in this context. The discussion highlights two distinct forms of otherness: alterity and diversity. While pluralistic and particularistic approaches to religious plurality emphasise diversities, Levinas’ ethics focus on the uniqueness of the other. This study examines the evolving landscape of religious plurality, emphasising the need for genuine openness and recognition of the religious other, and it probes the applicability of Levinas’ ethics to interreligious dialogue while recognising the complexities inherent in such encounters.